Ultrafine copper nanoclusters and single sites for Fenton-like reactions with high atom utilities. Issue 9 (5th August 2020) - Yin, Yu; Li, Wenlang; Xu, Chunli; Shi, Lei; Zhang, Lai-Chang; Ao, Zhimin; Liu, Mengxuan; Lu, Min; Duan, Xiaoguang; Wang, Shaobin; Liu, Shaomin; Sun, Hongqi
Abstract : Fenton-like degradation of p -hydroxybenzoic acid by ultrafine copper nanoclusters and single sites exhibited high atom utilities and a wide working pH range. Abstract : Catalysts containing both nanoclusters and single atom metal sites have received increasing attention because of their superior catalytic activities to their aggregated counterparts. Herein, ultrafine CuO nanoclusters along with Cu single atoms were anchored onto typical mesoporous silica SBA-15 for Fenton-like reactions, and the obtained catalysts were named UNCu-SBA. Both advanced characterization and computational studies offered convincing evidence for the unique structural feature. XPS and XANES identified the valence state of Cu(ii ) on UNCu-SBA. Fenton-like reactions further demonstrated that UNCu-SBA manifested higher activities in comparison with APCu-SBA, which contained aggregated CuO particles. Moreover, the Cu mass normalized rate constant of UNCu-SBA was 18 times larger than that of APCu-SBA, suggesting an exceptional Cu atom utility in UNCu-SBA. The UNCu-SBA catalyst was able to activate H2 O2 to generate ˙OH in a wider pH range of 4–7 than in typical Fenton reactions (2–4). This may direct future advances toward AOP nanocatalysis.